Quantitative calculation of a confocal synchrotron radiation micro-X-ray fluorescence imaging technique and application on individual fluid inclusion. Issue 11 (6th October 2021) - Lin, Xiao-Sheng; Zhang, Li-Li; Xu, Jiu-Hua; He, Yan; Zheng, Yi; Yan, Shuai; Liang, Dong-Xu; Li, Ai-Guo
Abstract : Elemental distribution representations at varying depths by the confocal μ-SRXRF imaging technique are effectively compensated for after quantitative calculation. Abstract : A confocal synchrotron radiation micro-X-ray fluorescence (μ-SRXRF) imaging setup based on Kirkpatrick–Baez (K–B) mirrors and polycapillary optics is described and characterized at the hard X-ray micro-focusing beamline (BL15U1) of the Shanghai Synchrotron Radiation Facility (SSRF). It provides a depth resolution of 10.2–26.5 μm in the energy range of 5.0–13.0 keV. A quantitative calculation method based on the fundamental parameter (FP) method was presented for elemental distribution images obtained with the confocal μ-SRXRF imaging setup. For each pixel of a depth-scanning measurement, quantitative calculation was performed considering the actual geometry of the setup and various emission paths of X-ray fluorescence (XRF). The initial inhomogeneous XRF intensity distribution maps from a National Institute of Standards and Technology (NIST) standard reference material (SRM) 611 form rather homogeneous concentration distribution maps after quantitative calculation. The combination of a confocal μ-SRXRF imaging technique with a quantitative calculation method is illustrated with the results of the analysis of an individual fluid inclusion within a natural beryl crystal. Non-destructive 3D XRF analysis by the confocal μ-SRXRF imaging technique will be effective for depth-structural and multi-elemental studies of many materials and allows studying more complicated phenomena.